Peirce's primary arithmetics: A brief presentation and some remarks on the translation of these manuscripts to Portuguese - Garnica, Antonio Vicente Marafioti [UNESP]; De Souza, Leandro Josué [UNESP]; Salandim, Maria Ednéia Martins [UNESP] (FapUNIFESP (SciELO), 2018)
This paper aimsto present the five manuscripts of the so-called Peirce's Primary Arithmetics(Lydia Peirce's Primary Arithmetic; Primary Arithmetic (with suggestions to teachers); Peirce's Primary Arithmetic upon the psychological method; C.S.Peirce's Vulgar Arithmetic: its main features, and Practical Arithmetic) and to sketch some remarks on the process of translating such manuscripts to Portuguese. This article is the last study related to some initial and brief hermeneutics already started in the other articles published by the same authors.
Dos Manuscritos da Aritmética Elementar de Charles S. Peirce:uma breve apresentação e algumas considerações sobre sua tradução
Keywords: Charles Sanders Peirce; History; Mathematics Education; Primary Arithmetics; Translation